ANALISIS PERHITUNGAN PENYUSUTAN ASET TETAP MENURUT PSAK NO. 216 (REVISI 2024) DAN PERATURAN MENTERI KEUANGAN SERTA DAMPAKNYA TERHADAP LAPORAN LABA RUGI PADA PT. XYZ KABUPATEN SUKABUMI TAHUN 2024 - Vina Syabilla; Andy Lasmana; Didi Didi (Investama : Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the calculation of fixed asset depreciation at PT. XYZ based on PSAK No. 216 (Revised 2024) and tax regulations stipulated in the Minister of Finance Regulation No. 72 of 2023, as well as to examine its impact on the company’s income statement and fiscal corrections. Fixed assets are a crucial component of manufacturing companies’ operational activities, as they have material value and long-term useful lives. Therefore, depreciation calculations significantly affect financial performance and corporate income tax obligations. This research employs a descriptive qualitative approach with a comparative analysis method by comparing fixed asset depreciation calculations based on company policies, PSAK No. 216 (Revised 2024), and PMK No. 72 of 2023. The data used are secondary data obtained from the company’s financial statements, fixed asset registers, and other supporting documents. The results indicate that, in general, the classification of fixed assets implemented by PT. XYZ complies with the provisions of PMK No. 72 of 2023. However, discrepancies were found in depreciation calculations, particularly for assets whose useful lives had expired but were still depreciated, as well as assets that were depreciated before being put into use. These differences led to variations in depreciation expense recognition between commercial and fiscal depreciation, affecting reported profit and resulting in positive fiscal corrections. Therefore, the company is required to improve the accuracy of its fixed asset depreciation calculations to ensure reliable and accurate financial reporting in accordance with applicable accounting standards and tax regulations.